Financial integration and its implication for economic union in Asia - Kumari , Sarinder; Habibullah, Muzafar Shah; Azali, M.; Yusoff, Mohammed; Yoke-Kee, Eng (Ashgate Publishing Limited, 2005)
This paper focuses on the savings-investment criterion as a way of measuring international capital mobility. The study uses data from 11 countries having different stages of financial and economic development. The results suggest that savings and investment are cointegrated. The saving retention coefficient is low suggesting that Asian countries have already satisfied one of the criteria of the optimum currency area.